2021
DOI: 10.1186/s13075-021-02568-x
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic estimation of monosodium urate burden predicts the fulfillment of the 2016 remission criteria for gout: a 12-month study

Abstract: Objective To investigate whether baseline monosodium urate (MSU) burden estimated by ultrasound (US) predicts the achievement of the 2016 remission criteria for gout after 12 months. Methods In this 12-month prospective, observational and single-center study, patients with gout fulfilling all the domains of the 2016 preliminary remission criteria for gout at baseline and on urate-lowering therapy (ULT) for at least the preceding 6 months were conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Ultrasound in gout has mainly been advocated for diagnosis ( 45 ), though some recent papers have proven an interesting role in monitoring the disease, such as checking the reduction of deposits during ULT ( 46 ), and predicting the occurrence of flares after discontinuation of colchicine ( 47 ) or the achievement of remission criteria in the following 12 months ( 48 ). Furthermore, ultrasound could also be of interest for establishing cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound in gout has mainly been advocated for diagnosis ( 45 ), though some recent papers have proven an interesting role in monitoring the disease, such as checking the reduction of deposits during ULT ( 46 ), and predicting the occurrence of flares after discontinuation of colchicine ( 47 ) or the achievement of remission criteria in the following 12 months ( 48 ). Furthermore, ultrasound could also be of interest for establishing cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with gout meeting the 2015 ACR/EULAR classification criteria and patients with a crystal-proven diagnosis of CPPD were consecutively recruited from among those participating in three US imaging studies. [8][9][10] These criteria were selected as the current and internationally recognised criteria for classifying patients as having gout or CPPD disease. Patients with mixed crystal arthritis were excluded from all studies.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…US assessments were carried out according to the 2017 EULAR standardised procedures for US imaging in rheumatology 11 by a rheumatologist blinded to patients' diagnosis. [8][9][10] The hyaline cartilage of the scanned joints was explored to detect US findings indicative of crystal deposits (ie, DC sign and CPP deposits within the cartilage layer), 1 12 paying particular attention to differentiate the DC sign from the cartilage interface sign, which is visible only when the outer margin of the hyaline cartilage is perpendicularly insonated by the US beam and usually is thinner than the DC sign and the bony cortex (figure 1). Furthermore, once a DC sign was identified, its dynamic behaviour during joint movement was evaluated while holding the probe steady (ie, movement of the DC sign together with the hyaline cartilage and the subchondral bone, indicating crystals attached on the cartilage surface or in the opposite direction, indicating crystals in the joint capsule Crystal arthropathies Crystal arthropathies Crystal arthropathies or ligaments) (online supplemental video S1 and online supplemental video S2).…”
Section: Us Assessmentmentioning
confidence: 99%
“…US can show resolution of urate deposits in patients on urate-lowering therapy with greater decrease of US tophus size and resolution of double-contour cartilage sign occurring in patients with lower serum urate levels than in those patients with higher serum urate levels [ 123 ]. It has been shown that the MSU crystal burden on US can predict fulfilling remission criteria for gout: the lower the baseline MSU burden estimated by US, the higher the chance to fulfil the remission criteria at 12 months, with the double-contour cartilage sign being the most useful measure [ 124 ]. Christiansen et al showed that US can detect decreases in urate crystal deposition (double contour sign, tophi, aggregates and erosions) in patients on successful urate-lowering therapy [ 125 ].…”
Section: Imaging Of Treatment Responsementioning
confidence: 99%